2009
DOI: 10.1016/j.pain.2009.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious affective processing and empathy: An investigation of subliminal priming on the detection of painful facial expressions

Abstract: Results from recent functional neuroimaging studies suggest that facial expressions of pain trigger empathic mimicry responses in the observer, in the sense of an activation in the pain matrix. However, pain itself also signals a potential threat in the environment and urges individuals to escape or avoid its source. This evolutionarily primitive aspect of pain processing, i.e., avoidance from the threat value of pain, seems to conflict with the emergence of empathic concern, i.e., a motivation to approach tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(148 citation statements)
references
References 23 publications
6
139
1
2
Order By: Relevance
“…Further, prior research shows reduced anticipation of and reactivity to pain stimuli in people with high CU traits (measured as psychopathy) [30,52]. In other words, people high on CU traits may not understand the pain experiences of other people [15] because of a lack of vicarious emotional experience [53]. Indeed, Caes and colleagues [30] showed that psychopathy was related to less sensitivity in detecting another person's pain.…”
Section: Discussionmentioning
confidence: 99%
“…Further, prior research shows reduced anticipation of and reactivity to pain stimuli in people with high CU traits (measured as psychopathy) [30,52]. In other words, people high on CU traits may not understand the pain experiences of other people [15] because of a lack of vicarious emotional experience [53]. Indeed, Caes and colleagues [30] showed that psychopathy was related to less sensitivity in detecting another person's pain.…”
Section: Discussionmentioning
confidence: 99%
“…Findings that another's pain activates neural representations of personal pain as well as self-oriented aversive emotional responses suggest that observing pain automatically references the self, potentially signaling threat to one's own physical integrity and non-pain goals [7,51,60]. Indeed, the seminal work of Yamada and Decety [95] suggested that observation of pain does not automatically activate empathic concern, but rather activates a threat detection system resulting in a general aversive response in the observer. Such findings may reflect the evolutionary roots of the intrinsically interpersonal nature of pain and underscore that pain touches on multiple goals relevant to not only persons-in-pain but also observers.…”
Section: The Relationship Between Emotion and Motivation In Painmentioning
confidence: 99%
“…The present study extends previous research by investigating observers' reactions in a more salient interpersonal context. Specifically, instead of using pictures, videotaped models/confederates or avatars 13,15,16,72,78,81 , observers watched a real-life participant undergoing painful stimulation.…”
Section: Self-report Datamentioning
confidence: 99%
“…Furthermore, research on personal pain experience has consistently shown that participants display a fear-potentiated startle when experiencing or 18 anticipating pain 25,38,41,47 , particularly when pain is perceived as highly threatening 7 Observers' distress towards pain signals in others likely serve a protective function of preparing observers for dealing with impending threat 40 . Specifically, observers' distress responses may instigate avoid/escape tendencies 72,81 . Such defensive tendencies seem to be in conflict with the often-observed emergence of other-oriented emotions (e.g., sympathy) and associated approach tendencies when viewing others in pain 35 .…”
Section: Self-report Datamentioning
confidence: 99%
See 1 more Smart Citation